2014
DOI: 10.1002/ange.201405761
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Dynamic Combinatorial Chemistry, and PCR Amplification of 3′–5′ and 3′–6′ Disulfide‐linked Oligonucleotides

Abstract: Disulfide dithymidines linked 3′–5′ or 3′–6′ were synthesized and incorporated into oligonucleotides through a combined phosphotriester and phosphoramidite solid‐phase oligonucleotide synthesis approach. The disulfide links are cleaved and formed reversibly in the presence of thiols and oligonucleotides. This link was shown to be sequence‐adaptive in response to given templates in the presence of mercaptoethanol. The artificial 3′–5′ and 3′–6′ disulfide link was tolerated by polymerases in the polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In cell‐penetrating poly(disulfide)s (CPDs) such as 2 ,[7] the peptide backbone of CPPs is replaced by a disulfide polymer [8 – 13]. This is of interest to i ) prepare the transporters in situ by ring‐opening disulfide‐exchange polymerization,[7] ii ) destroy the transporters upon arrival in the cytosol by reductive depolymerization to minimize toxicity and liberate the native substrate,[8] and iii ) integrate new uptake mechanisms ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In cell‐penetrating poly(disulfide)s (CPDs) such as 2 ,[7] the peptide backbone of CPPs is replaced by a disulfide polymer [8 – 13]. This is of interest to i ) prepare the transporters in situ by ring‐opening disulfide‐exchange polymerization,[7] ii ) destroy the transporters upon arrival in the cytosol by reductive depolymerization to minimize toxicity and liberate the native substrate,[8] and iii ) integrate new uptake mechanisms ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“… 18 A detailed study revealed several molecular characteristics of artificial backbones that are required for compatibility with DNA polymerases during replication. 19 Such polymerase compatible artificial backbones comprise 5′- S -phosphorothioesters, 20 phosphorothioates, 21 disulfides, 22 boranophosphates, 23 phosphoramidates, 10 , 24 , 25 amides, 19 , 26 ureas, 18 squaramides, 18 and triazoles. 8 , 9 , 19 , 27 29 Among these, the triazole linkage (TL) represents a powerful and versatile chemical moiety that can be readily formed by the Cu I -catalyzed azide–alkyne cycloaddition (CuAAC) reaction, resulting in 1,4-disubstituted 1,2,3-triazoles.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, π stacking can enhance the catalytic activity of complexes containing a pyrene moiety; 34 rational ligand design 35,36 or by a wise choice of the counterion. 37−43 Indeed, the interplay between covalent and noncovalent interactions recently led to interesting results in dynamic combinatorial library-driven synthesis 44−46 (also applied to biomolecules 47,48 ), surface chemistry, 49,50 and reactivity of halogen-containing moieties. 51 More specifically, the presence of a noncovalent interaction can influence the covalency of a chemical bond.…”
Section: ■ Introductionmentioning
confidence: 99%